'He failed to find his place in this school' – re-examining the role of teachers in bullying in a Finnish comprehensive school. Issue 1 (2nd January 2020) - Juva, Ina; Holm, Gunilla; Dovemark, Marianne
ABSTRACT: Bullying has been conceptualised as a phenomenon that focuses mainly on individuals and individual behaviour. We seek to broaden the discussion on bullying by describing and defining how teachers participate in and/or enable bullying, and to thus expand the notion of bullying as individual behaviour to include actors, norms and processes. This study is based on ethnographic observation and interview data that were gathered in 2013–2016 in one high school in the metropolitan area of Finland. We found that teachers ignored and excluded a student who was labelled 'not-normal'. We use the concept of recognition and redefine it according to the context of bullying, and state that the individual in our study was not recognised as a student because he broke the norms of the school and was thus excluded. We suggest that bullying should be seen as a structural issue and should not be limited to individuals' behaviour.